2018
DOI: 10.1007/s00464-018-6329-3
|View full text |Cite
|
Sign up to set email alerts
|

Robotic transanal minimally invasive surgery (TAMIS) with the newest robotic surgical platform: a multi-institutional North American experience

Abstract: With increased reach and operative range of motion, Robotic TAMIS is a safe and effective method for excising low-risk rectal neoplasia with a wide range of anatomical measurements. Higher BMI is a significant predictor of a longer and likely more challenging operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 22 publications
1
56
0
Order By: Relevance
“…A recent observational study has identified that in the United Kingdom a smaller proportion of patients with acute cholecystitis (of any age group) receive emergency cholecystectomy on their index admission compared to the United States (Rate of emergency cholecystectomy in UK 15.7 vs. 52.7% in USA) [ 26 ]. Previous studies from the United Kingdom have recommended that elderly patients with acute cholecystitis should be managed conservatively due to the potentially significant risk of post-operative morbidity in these patients, and interval cholecystectomy be reserved for those with recurrent episodes of cholecystitis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent observational study has identified that in the United Kingdom a smaller proportion of patients with acute cholecystitis (of any age group) receive emergency cholecystectomy on their index admission compared to the United States (Rate of emergency cholecystectomy in UK 15.7 vs. 52.7% in USA) [ 26 ]. Previous studies from the United Kingdom have recommended that elderly patients with acute cholecystitis should be managed conservatively due to the potentially significant risk of post-operative morbidity in these patients, and interval cholecystectomy be reserved for those with recurrent episodes of cholecystitis [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2012, several studies reporting the outcomes of R-TAMIS were published, but they included many case reports and small series of patients [2,[35][36][37][38][39][40][41] . The largest series was published by Tommasi et al [40] in 2019 and included overall 58 patients.…”
Section: Robotic Transanal Surgerymentioning
confidence: 99%
“…Some useful data are also provided by the second largest series found about R-TAMIS, published by Liu et al [36] in 2018 and including 34 patients. All cases reported were performed using a Da Vinci Xi technology and a GelPOINT platform.…”
Section: Robotic Transanal Surgerymentioning
confidence: 99%
“…We believe that, at any rate, the significance of the transanal approach will endure, particularly in cases with difficulty via the transabdominal approach, whether open, laparoscopic, or robotic 54) . Recently, transanal use of robotic platforms has been reported to reduce the limitations of the ergonomics of single-port surgery [61][62][63][64] . Furthermore, with the advent of robotic platforms designed for single-port surgery, robotic transanal surgery has been expected to overcome the limitations of single-port surgery 61,62,64) .…”
Section: Future Prospectsmentioning
confidence: 99%